Stakeholder value‐linked sustainability assessment: Evaluating remedial alternatives for the Portland Harbor Superfund Site, Portland, Oregon, USA. (6th December 2017) - Apitz, Sabine E; Fitzpatrick, Anne G; McNally, Amanda; Harrison, David; Coughlin, Conor; Edwards, Deborah A
ABSTRACT: Regulatory decisions on remediation should consider affected communities' needs and values, and how these might be impacted by remedial options; this process requires that diverse stakeholders are able to engage in a transparent consideration of value trade‐offs and of the distribution of risks and benefits associated with remedial actions and outcomes. The Stakeholder Values Assessment (SVA) tool was developed to evaluate remedial impacts on environmental quality, economic viability, and social equity in the context of stakeholder values and priorities. Stakeholder values were linked to the pillars of sustainability and also to a range of metrics to evaluate how sediment remediation affects these values. Sediment remedial alternatives proposed by the US Environmental Protection Agency (USEPA) for the Portland Harbor Superfund Site were scored for each metric, based upon data provided in published feasibility study (FS) documents. Metric scores were aggregated to generate scores for each value; these were then aggregated to generate scores for each pillar of sustainability. In parallel, the inferred priorities (in terms of regional remediation, restoration, planning, and development) of diverse stakeholder groups (SGs) were used to evaluate the sensitivity and robustness of the values‐based sustainability assessment to diverse SG priorities. This approach, which addresses social indicators of impact and then integrates them with indicators of environmental and economic impacts, goes well beyond the Comprehensive Environmental Response, Compensation and Liability Act's (CERCLA) 9 criteria for evaluating remedial alternatives because it evaluates how remedial alternatives might be ranked in terms of the diverse values and priorities of stakeholders. This approach identified trade‐offs and points of potential contention, providing a systematic, semiquantitative, transparent valuation tool that can be used in community engagement. Integr Environ Assess Manag 2018;14:43–62. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: The Stakeholder Values Assessment (SVA) tool was developed as a sediment remediation–specific multicriteria assessment tool and used to evaluate trade‐offs between environmental, economic, and social costs and benefits of Portland Harbor Superfund Site remedial alternatives. The tool links environmental quality, economic viability, and social equity metrics to a range of stakeholder values; metrics were scored and aggregated and options were ranked in terms of stakeholder group (SG) priorities. There are progressively lower net scores for the larger alternatives; small incremental decreases in risk for more aggressive alternatives are outweighed by the increased net environmental, economic, and social costs and impacts. The tool is sensitive to stakeholder inputs—the relative value and pillar scores change in response to different SG priorities, identifying trade‐offs, opportunities for optimization, and sources of potential disagreement—providing a systematic, transparent valuation tool for community engagement.